EISCAT-Cluster observations of quiet-time near-Earth magnetotail fast flows and their signatures in the ionosphere - Pitkänen, T.; Aikio, A. T.; Amm, O.; Kauristie, K.; Nilsson, H.; Kaila, K. U. (Annales Geophysicae, 2011)
We report observations of a sequence of quiet-time Earthward bursty bulk flows (BBFs) measured by the Cluster spacecraft in the near-tail plasma sheet (XGSM ~ −12 to −14 RE) in the evening sector, and by simultaneous high-resolution measurements in the northern conjugate ionosphere by the EISCAT radars, a MIRACLE all-sky camera and magnetometers, as well as a meridian-scanning photometer (MSP) in the Scandinavian sector on 17 October 2005. The BBFs at Cluster show signatures that are consistent with the plasma "bubble" model (Chen and Wolf, 1993, 1999), e.g. deflection and compression of the ambient plasma in front of the Earthward moving bubble, magnetic signatures of a flow shear region, and the proper flows inside the bubble. In addition, clear signatures of tailward return flows around the edges of the bubble can be identified. The duskside return flows are associated with significant decrease in plasma density, giving support to the recent suggestion by Walsh et al. (2009) of formation of a depleted wake. However, the same feature is not seen for the dawnside return flows, but rather an increase in density. In the ionosphere, EISCAT and optical measurements show that each of the studied BBFs is associated with an auroral streamer that starts from the vicinity of the polar cap boundary, intrudes equatorward, brakes at 68–70° aacgm MLAT and drifts westward along the proton oval. Within the streamer itself and poleward of it, the ionospheric plasma flow has an equatorward component, which is the ionospheric manifestation of the Earthward BBF channel. A sharp velocity shear appears at the equatorward edge of a streamer. We suggest that each BBF creates a local velocity shear in the ionosphere, in which the plasma flow poleward of and inside the streamer is in the direction of the streamer and southeastward. A northwestward return flow is located on the equatorward side. The return flow is associated with decreased plasma densities both in the ionosphere and in the magnetosphere as measured by EISCAT and Cluster, respectively. In summary, we present the first simultaneous high-resolution observations of BBF return flows both in the plasma sheet and in the ionosphere, and those are in accordance with the bubble model. The results apply for the duskside return flows, but the manifestation of dawnside return flows in the ionosphere requires further studies. Finally, EISCAT measurements indicate increased nightside reconnection rate during the ~35-min period of BBFs. We suggest that the observed temporal event of IMF rotation to a more southward direction produces enhanced open flux transport to the nightside magnetotail, and consequently, the nightside reconnection rate is increased.